Materialidade e conflito : visões sobre corporalidade e o objeto artístico por três artistas latino-americanas, Janine Antoni, Teresa Margolles e Doris Salcedo - Contreras Godínez, Mónica Elisa (2017)
This thesis aims to bring up a reflection upon the contemporary artistic production in three latin-american artists, specifically Janine Antoni (Bahamas, 1962), Teresa Margolles (México,1963- ) and Dóris Salcedo (Colômbia 1958-), this artists explore noti